(untitled) (Global Journal of Medical Research, 2022)
An increase in the life span leads to population aging and an increase in neurodegenerative and cerebrovascular lesions. In the treatment of neurodegenerative and cerebrovascular diseases, it is advisable to stimulate angiogenesis and neurogenesis thereby causing cerebral tissues regeneration. Photobiomodulation Therapy (PBMT) is a promising direction in this area. This work is dedicated to the clinical application of transcatheter intracerebral laser PBMT for stimulating angiogenesis and neurogenesis in various Alzheimer’s disease (AD) stages.